2019
DOI: 10.1186/s12875-019-0992-x
|View full text |Cite
|
Sign up to set email alerts
|

Communication practices for delivering health behaviour change conversations in primary care: a systematic review and thematic synthesis

Abstract: Background Clinical guidelines exhort clinicians to encourage patients to improve their health behaviours. However, most offer little support on how to have these conversations in practice. Clinicians fear that health behaviour change talk will create interactional difficulties and discomfort for both clinician and patient. This review aims to identify how healthcare professionals can best communicate with patients about health behaviour change (HBC). Methods We include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 40 publications
(155 reference statements)
2
42
0
Order By: Relevance
“…In the WRAP trial we observed that less than half of participants who received free vouchers to attend the programme for 1 year continued to do so over the last 12 weeks of the 1-year treatment [6], and providers could use regular attendance as a criterion for continued provision of services to improve the cost-effectiveness of these interventions. Future research should address how practitioners can support ongoing attendance, perhaps learning from prior research on communication practices to deliver health behaviour change [28].…”
Section: Discussionmentioning
confidence: 99%
“…In the WRAP trial we observed that less than half of participants who received free vouchers to attend the programme for 1 year continued to do so over the last 12 weeks of the 1-year treatment [6], and providers could use regular attendance as a criterion for continued provision of services to improve the cost-effectiveness of these interventions. Future research should address how practitioners can support ongoing attendance, perhaps learning from prior research on communication practices to deliver health behaviour change [28].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is extensive literature regarding the methods of communication about weight management and behaviour change in clinical practice [69][70][71] , a key source of our statement comes from the inclusion of expert groups living with obesity, represented by Obesity UK.…”
Section: Data Sources For Compiling This Guidelinementioning
confidence: 99%
“…Another review of patientnurse communication studies, focusing on CA and ethnomethodology, searched three databases for all literature through 2016 and found only 40 articles (Mayor & Bietti, 2017). Patient education researchers exhibit similar patterns, with very few studies using CA (Albury et al, 2019;Murad et al, 2014;Stortenbeker et al, 2020).…”
Section: Introductionmentioning
confidence: 99%